El nacionalismo a través de la fiesta cívica. Reconfiguración simbólica del ritual, espacios y actores: Morelia 1940-1952 - Kuk Soberanis, Gabriela Guadalupe (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The present investigation tries to identify from the civic festivity the fundamental elements of the nationalism that permeated the Morelian society in the forties of the 20th century. It is a reflection on the prevailing discourse of the time of national unity, the pedagogy of democratic values and the reforms to the legislation that allowed establishing the parameters for the identification of nationalist elements in the civic festivities that the inhabitants of Morelia enjoyed. It addresses the local festive rite from its reconfiguration, the protocol civic acts and its playful counterpart. Analyze the conformation of civic commemorations to understand post-revolutionary nationalism. The civic festivity acquired an incipient nationalist nuance from its fight for independence in the year 1810. With the passing of the 19th century, the ritual added symbols, myths, sacrificial passages and, above all, tints of heroism. Hence its complexity and redefinition with symbolic elements such as the flag, the shield and the national anthem. By the 20th century, in Mexico in 1940, the federal, state and local ruling class incorporated pre-Hispanic, colonial and independence elements into the civic discourse; The historical facts and events that revolutionized the history of Mexico from the colonial era to the 20th century, were incorporated into the narrative, causing that reconfiguration that favored tradition and could be celebrated without the threat of being obsolete. As we will see later, the Mexican state not only made use of the civic calendar and the confidence in its federal and state authorities to carry them out. The nationalism manifested in the civic celebration should be incorporated into the formation of the Mexican citizen; If the era of institutions had broken in to order the life of society, it also had to take responsibility for its education.

El presente de investigación pretende identificar a partir de la festividad cívica los elementos fundamentales del nacionalismo que permeo en la sociedad moreliana en la década de los cuarenta del siglo XX. Es una reflexión sobre el discurso imperante de la época de la unidad nacional, la pedagogía de los valores democráticos y las reformas a la legislación que permitieron establecer los parámetros para la identificación de los elementos nacionalistas en las festividades cívicas que disfrutaban los habitantes Morelia. Aborda el rito festivo local desde su reconfiguración, los actos cívicos protocolarios y su contraparte lúdica. Analiza la conformación de las conmemoraciones cívicas para comprender al nacionalismo post revolucionario. La festividad cívica adquirió un incipiente matiz nacionalista a partir de su lucha por la independencia en el año de 1810. Con el transcurrir del siglo XIX, el ritual adhirió símbolos, mitos, pasajes de sacrificio y sobre todo tintes de heroicidad. De ahí su complejización y resignificación con elementos simbólicos como la bandera, el escudo y el himno nacional. Ya para el siglo XX, en el México de 1940, la clase gobernante tanto federal como estatal y local, incorporó elementos prehispánicos, coloniales e independentistas al discurso cívico; los hechos históricos y los acontecimientos que revolucionaron la historia de México de la época colonial hasta el siglo XX, se incorporaron a la narrativa provocando esa reconfiguración que favoreció a la tradición y pudiesen celebrarse sin la amenaza de ser obsoleta. Como veremos más adelante, el estado mexicano no sólo hecho mano del calendario cívico y de la confianza en sus autoridades federales y estatales para realizarlas. El nacionalismo manifestado en la celebración cívica debía incorporarse a la formación del ciudadano mexicano; si la era de las instituciones había irrumpido para ordenar la vida de la sociedad, ésta también debía responsabilizarse de su educación.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-D-2023-0895; Nación; Festividad; Actos oficial; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16558